Between the Enemy and Texas : Parsons's Texas Cavalry in the Civil War - Bailey, Anne J. (Book collections on Project MUSE., 1989)
Much of the Civil War west of the Mississippi was a war of waiting for action, of foraging already stripped land for an army that supposedly could provision itself, and of disease in camp, while trying to hold out against Union pressure. There were none of the major engagements that characterized the conflict farther east. Instead, small units of Confederate cavalry and infantry skirmished with Federal forces in Arkansas, Missouri, and Louisiana, trying to hold the western Confederacy together. The many units of Texans who joined this fight had a second objective -- to keep the enemy out of their home state by placing themselves "between the enemy and Texas." Historian Anne J. Bailey studies one Texas unit, Parsons's Cavalry Brigade, to show how the war west of the Mississippi was fought. Historian Norman D. Brown calls this "the definitive study of Parsons's Cavalry Brigade; the story will not need to be told again." Exhaustively researched and written with literary grace, Between the Enemy and Texas is a "must" book for anyone interested in the role of mounted troops in the Trans-Mississippi Department